Penanaman Sikap Spiritual dan Sosial Peserta Didik pada Pembelajaran Pendidikan Agama Islam di Sekolah Menengah Pertama Islam Terpadu - Naswiyah, Naswiyah (Al-Miskawaih: Journal of Science Education, 2023)
This research discusses Islamic religious education learning in instilling spiritual attitudes and social attitudes. The focus of the study in this article is how Islamic Religious Education learning is directed at instilling spiritual attitudes and social attitudes in students at SMP IT Insan Harapan, Batam City. This article originates from descriptive qualitative research. Data was obtained by observation, interviews and documentation. The research results show that the cultivation of spiritual attitudes is carried out with the principle that the implementation of learning and school activities is shown to meet the indicators of spiritual attitudes and social attitudes. Methods that are often used include; exemplary methods, refraction, motivation, and cultivation of spiritual and social attitudes in schools. Supporting factors for cultivating spiritual and social attitudes include; intensive coaching, culture, types of activities, and adequate school facilities. Penelitian ini membahas tentang pembelajaran pendidikan agama Islam dalam menanamkan sikap spiritual dan sikap sosial. Fokus kajian dalam artikel ini adalah bagaimana pembelajaran Pendidikan Agama Islam diarahkan untuk menanamkan sikap spiritual dan sikap sosial peserta didik di SMP IT Insan Harapan Kota Batam. Artikel ini berasal dari penelitian kualitatif deskriptif. Data diperoleh dengan cara observasi, wawancara, dan dokumentasi. Hasil peneitian menunjukkan bahwa penanaman sikap spiritual dilakukan dengan prinsip bahwa pelaksanaan pembelajaran dan kegiatan sekolah ditunjukkan untuk memenuhi indikator sikap spiritual dan sikap sosial. Metode yang sering dijalankan antara lain; metode keteladanan, pembiasan, motivasi, dan pembudayaan sikap spiritual dan sosial di sekolah. Faktor pendukung penanaman sikap spiritual dan sosial antara lain; intensifnya pembinaan, budaya, jenis kegiatan, dan sarana sekolah yang memadai.